Evaluation of radiation dose to cardiac and pulmonary tissue among patients with stage IV Wilms tumor and pulmonary metastases. Issue 8 (28th February 2014) - Farooqi, Ahsan; Siddiqi, Arsalan; Khan, Mohammad K.; Esiashvili, Natia
<x xml:space="preserve">Abstract</x> Background Most patients with stage IV Wilms tumor (WT) and pulmonary metastases are treated with surgery, local radiotherapy (RT), and whole‐lung irradiation (WLI). The Children's Oncology Group is studying whether WLI should only be given if metastatic lung lesions persist following induction chemotherapy. We hypothesized that radiation dose to cardiac and pulmonary organs are increased when WLI and abdominal RT fields are administered sequentially. Procedure We retrospectively identified 16 patients with stage IV WT and pulmonary metastases to model dosimetry plans for concurrent and sequential flank or whole abdomen and whole‐lung fields. Results Treatment plans were evaluated for dosimetric endpoints to the heart and the lungs. The mean dose (Gy) was significantly higher to the heart (15.8 vs. 12.1, P < 0.0001) and lungs (14.1 vs. 12.2, P < 0.0002) when patients with stage IV WT and pulmonary metastases were treated with sequential RT. The percent tissue organ volumes (V) receiving high RT doses of 15 and 20 Gy (V15 and V20) were negligible in concurrent treatment plans. Comparatively, mean V15 and V20 values for sequential treatment plans were 35% and 27%, respectively, for the heart, and 15% and 12%, for the lungs. Conclusions The dose to the heart and lung tissue is significantly increased when WLI and abdominal RT fields are administered sequentially. While omission of WLI may be beneficial for patients achieving good response to induction chemotherapy, the less favorable response group may be subjected to increased risk of cardiac and pulmonary toxicities from sequential WLI. Pediatr Blood Cancer 2014; 61:1394–1397. © 2014 Wiley Periodicals, Inc.